Prospects for Transparency In International Commercial Arbitration: Will Indonesia Rise to The Challenge of Introducing Transparency Into Its Arbitration System? - Evelyn (Mahadi: Indonesia Journal of Law, 2023)
This paper weighs the pros and cons of confidentiality in arbitration and discusses how transparency can enhance the legitimacy of arbitration. Find out how the players can contribute to promote transparency. How arbitration bodies, parties to arbitration, and legislative bodies contribute to promoting predictability and legitimacy in international commercial arbitration (ICA) without sacrificing confidentiality. Explore the possibility of arbitration joining the ICA trend towards transparency. Finally, itdiscusses the possibility of publishing the full award, and whether Section 69 of the English Arbitration Act could be a better solution to promote transparency and accountability.